Efficacy of Application of Periodontal Ligament Stem Cells in Bone Regeneration: A Systematic Review of Animal Studies - Pardis Aghandeh; Farnaz Kouhestani; Fatemeh Isamorad; Solmaz Akbari; Behrad Tanbakuchi; Saeed Reza Motamedian (Wolters Kluwer Medknow Publications, 2022)
Introduction: We aimed to systematically review the animal studies that have investigated the efficacy of periodontal ligament stem cells (PDLSCs) in bone regeneration. Methods: Web of science, Scopus, PubMed, Embase, Cochrane Library, and ProQuest were searched to September 2022 for animal studies investigating bone regeneration using PDLSCs. Results: Twenty studies were included. Calvaria and alveolar defects were treated with stem cells. The cells were mainly carried with hydrogel, hydroxyapatite, and collagen scaffolds. PDLSCs promoted osteogenesis compared with cell-free scaffolds, except in one study where biphasic calcium phosphate block scaffolds alone or with Bone morphogenic protein 2 had superior outcomes in calvaria defects. Controversial results were reported when comparing the osteogenic potential of PDLSCs and bone marrow stem cells. Two studies reported higher potential in BMSCs, and two others reported higher bone formation and more bone quality in PDLSCs. Conclusion: With the limitations of this study, PDLSCs might have promising potential to accelerate bone regeneration in artificial defects; however, due to high heterogeneity in the outcomes of the present studies, before moving forward to human experiments, further preclinical in vivo studies are needed.